Sosialisasi Pangan Aman, Sehat, Utuh, Halal (ASUH) dan Keamanan Jajanan Anak di Komunitas Belajar Gratis Rumah Sejuta Mimpi - Soru, Joanivita Paulo Gulo; Lalong, Paulus Risan Funan; Naben, Maria Novalina (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2025)
Food is an essential need for humans, especially school-age children. School-age children generally have PJAS (School Children's Snacks). However, PJAS is very vulnerable to the risk of contamination which can harm the consumers. Therefore, efforts must be made to increase children's knowledge about food safety. ASUH (safe, healthy, whole and halal) food can be selected to ensure the safety of raw food materials. Meanwhile, CEK KLIK can be done for snacks and packaged foods. This socialization aims to increase understanding of food safety which includes ASUH Food and snack-food safety among the children of the Rumah Sejuta Mimpi Community. The implementation of this service activity consists of 3 stages, namely the preparation stage, implementation stage and evaluation stage. The methods used at the implementation stage included interactive lecture methods and discussions regarding ASUH Food, Safe Snacks and CEK KLIK, and demonstrations on making cassava and tuna fish fritters from local ingredients. Based on the results of the evaluation using the question-and-answer method, the results showed that 53% of children could answer correctly, 17% answered with hesitation or errors and 30% of children could not answer the questions correctly. Meanwhile, the results of the presentation showed that there was 1 group that got a score of 100% doing CEK CLIK, 2 groups got a score of 87.5% and 2 groups got a score of 75%. Follow-up recommendations that can be made are the continuation of practicing the knowledge children in this community have gained, strengthening the role of the community as food safety advocates and increasing the role of parents/guardians of children in the community to obtain information and supervision related to food safety.